Current Targeted Therapies for the Fight against Non-Small Cell Lung Cancer - Mustachio, Lisa Maria (Pharmaceuticals (Basel), 2020)
Lung cancers contribute to the greatest number of cancer-related deaths worldwide and still pose challenges in response to current treatment strategies. Non-small cell lung cancer (NSCLC) accounts for over 85% of lung cancers diagnosed in the United States and novel therapeutics are needed for the treatment of this disease. First and second generation targeted therapies against specific mutated or rearranged oncogenes in NSCLCs show anti-tumor activity and also increase survival. However, many NSCLC patients eventually develop resistance to these therapies or do not properly respond if they have central nervous system metastases. Thus, this review summarizes recent developments and findings related to the generation of novel targeted therapies recently or currently being developed to tackle hurdles that prior therapies were not able to overcome.